Composing music for anime: a case study of “Your Name” by Comix Wave Film / Amirul Aiman Mohd Hamdan - Mohd Hamdan, Amirul Aiman (2020)
This paper study on the musical piece composition titled “Sparkle” from the animation movie “Kimi No Nawa” which has brought a phenomenal feedback from the world on its context and composition secrets – as many recognition has been established for this movie as well as the piece itself. Hence the author has successfully unrevealed the key factor that makes this piece an international hits in both artistic point of view as well as the technical point of view. In the end, this piece has successfully portray a mix-emotional vibes to all its listeners’ nonexclusive to the animation-enthusiast, but also towards those industrial analyst – such as musical institutions and musical practitioners.